2019
DOI: 10.1093/ejcts/ezz305
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of solid-part tumour volume doubling time in patients with radiological part-solid or solid lung cancer

Abstract: OBJECTIVES The measurement of part-solid and whole tumour sizes in patients with non-small-cell lung cancer (NSCLC) using computed tomography (CT) has been widely accepted for assessing clinical outcomes. Although the volume doubling time (VDT) of a tumour is useful for distinguishing high-risk nodules from low-risk ones, it remains to be clarified whether separate calculation of whole-tumour VDT and solid-part tumour VDT (SVDT) greatly affects the survival rate of patients with radiologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…VDT has been largely utilized as a diagnostic biomarker to discriminate malignant and benign nodules [8,31,53]; however, the thresholds to discriminate between malignant and benign pulmonary nodules are inconsistent. Additionally, prior studies utilized VDT as a biomarker to differentiate between indolent and aggressive lung cancers diagnosed [5,21,36,50,51] and have also utilized VDT as a prognostic factor [32,40,49]. For example, a VDT of less than 400 days was found to be an independent risk factor for poor disease-free survival [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDT has been largely utilized as a diagnostic biomarker to discriminate malignant and benign nodules [8,31,53]; however, the thresholds to discriminate between malignant and benign pulmonary nodules are inconsistent. Additionally, prior studies utilized VDT as a biomarker to differentiate between indolent and aggressive lung cancers diagnosed [5,21,36,50,51] and have also utilized VDT as a prognostic factor [32,40,49]. For example, a VDT of less than 400 days was found to be an independent risk factor for poor disease-free survival [32].…”
Section: Discussionmentioning
confidence: 99%
“…In a study based on chest x-rays, the 5-year survival rate of fast-growing nodules with a VDT of < 113 days was associated with significantly lower than slow-growing nodules with a VDT > 113 days [49]. Setojima et al separated whole tumor VDT (WVDT) and solid-part tumor VDT (SVDT) and identified cut-offs 214 days for WVDT and less than 215 days for SVDT that were associated with poor recurrence-free survival and overall survival [40]. The decision tree in our analysis identified novel VDT thresholds (VDTs of 234 and 279) that exhibited independent capacity to discriminate between high-risk/aggressive tumors and low-risk/indolent tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Using a method similar to ours, they obtained solid-part tumor volume doubling times and concluded that there was a signi cantly higher 5-year recurrence-free survival rate in the group with VDTs > 215 days. [13] However, they did not include those who underwent segmentectomy or wedge resection. Thus, different inclusion criteria for patients may cause different VDT cut-off points.…”
Section: Discussionmentioning
confidence: 99%
“…Of the proximal-type, only 2 cases of pleural origin have been reported [ 7 , 8 ]. Previous lung cancer studies reported that the average solid-part tumor volume doubling time is 394~458 days [ 9 , 10 ]. In the present case, the volume of the tumor that had disseminated outside the thorax due to drainage was measured using the SYNAPSE VINCENT 3D volume analyzer (Fuji Medical Systems, Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 99%